Effect of Approximal Tooth Surface Morphology on the Formation of Overhang Filling of 2nd Class - P. Bednář; S. Ságlová; D. Černý; P. Závodský; O. Zmátlová; P. Pršalová; M. Hadravová (Czech Dental Chamber, 2006)
A relationship between approximal tooth surface morphology and creation of overhang filling is displayed. After drilling of approximal cavity, the gingival cavity margin was evaluated as concave or non-concave. After making the filling, on bite wing radiogram the filling quality was evaluated. The overall percentage of overhang filling in our study (up to 1mm of everhang material) was 6.36%, much less then could be found in literature (16-85% according the diagnostic method). There was not proven any statistical relationship between the risk of making overhang filling and approximal tooth morphology.